Legal Aspects in the Development and Management of the Bilaporah Area, Bangkalan, Madura - Nur Komariyah; Abdur Rohman (JUSTICES: Journal of Law, 2024)
This study aims to analyze the legal aspects in the development and management of the Bilaporah area in Bangkalan, Madura. This area has significant economic and tourism potential, but legal challenges often hinder the optimization of its development. This study identifies various relevant regulations, including agrarian law, environmental law, and regional regulations. In addition, this study evaluates the implementation of these policies in practice and the obstacles faced by local governments and investors. The results of the study indicate that unclear regulations and overlapping regulations often lead to legal uncertainty, which negatively affects the investment climate. Therefore, it is necessary to harmonize regulations and increase the capacity of law enforcement to support sustainable and equitable development in Bilaporah.